Reforming the WTO to defuse potential trade conflicts in genetically modified goods - Perdikis, Nicholas (2001)
Attempts to show that, firstly the US view of Europe's regulatory regime is misplaced and that the EU's developing policies are based on preferences expressed by consumers rather than producers' interests. Argues that the existing WTO agreements on Sanitary and Phyto-sanitary Measures and Technical Barriers to Trade, while established to provide consumers with protection, are ill-equiped to deal with current expressions of consumer preferences. Opines that new negotiations are required if the WTO is to be able to respond effectively to the new technology.